Principles Of Methodological Training Of Physics Students Based On Subjective-Reflective Education - Shokir Khudoynazarovich Berdiyev (Euro Asian Journal Publishing, 2024)
The article highlights the principles of methodological training of physics students based on subjective-reflective learning, highlighting their importance in the future work of students.
Keywords: humanitarian-technological approach; educational strategy